Formation of a subero-lignified apical deposit in root tip of radish (Raphanus sativus) as a response to copper stress. (10th February 2018) - Kováč, Ján; Lux, Alexander; Vaculík, Marek
Abstract: Background and Aims: Heavy metals induce changes in root metabolism and physiology, which can lead to a complex remodelling of the root system. The final morphological responses of radish ( Raphanus sativus ) roots exposed to toxic concentrations of the heavy metal (Cu) include root growth inhibition, differentiation of xylem vessels close to the root tip, enhanced suberin lamellae deposition and enhanced lateral root production. Recently, we have found that such changes in root morphology and anatomy are coupled to the formation of a subero-lignified apical deposit (SLAD) very close to the root tip. Methods: To clarify the details of the formation of a SLAD in the root tip, we conducted experiments with radish roots exposed to a high Cu concentration (60 µm ). Histochemical analysis of lignin and suberin as well as analysis of spatial–temporal characteristics of SLAD formation were performed by bright-field, fluorescence and confocal microscopy. Key Results: This unique structure, not longer than 100 µm, consists of modified cell walls of the central cylinder that are encircled by a short cylinder of prematurely suberized endodermal cells. A SLAD starts to form, in both primary and lateral roots, after cessation of root elongation, and it is coupled with xylem differentiation and root branching close to the root apex. We noticed that deposition of phenolic substances into a SLAD, mainly suberin in the endodermis, is spatially separated from suberization or lignification in basally located endodermis. Conclusions: Although the main reason for formation of a SLAD is elusive, we suggest that it is a part of stress-induced responses which relate to decreased root growth or permeability in heavy metal stress.